RESTRUKTURISASI KPR BERDASARKAN PERATURAN OTORITAS JASA KEUANGAN NOMOR 11/POJK/03/2020 TENTANG STIMULUS PEREKONOMIAN NASIONAL DAMPAK PENYEBARAN CORONAVIRUS DISEASE 2019 DI PT. BANK MAYBANK CABANG BSD KOTA TANGERANG SELATAN - Fergal Ramadhan Guskar; Moch Bukhori Muslim; Maulana Hasanudin (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
The primary issue with this study is the government's issuance of OJK 11/POJK/03/2020 on Countercyclical Impact Economic Stimulus. The propagation of Coronavirus Disease 2019 as a kind of government support for COVID-19-afflicted Indonesians. Banks in Indonesia are required to carry out relief/restructuring of bank credit services. If Bank Maybank South Tangerang City BSD branch delivers relief/restructuring, is it in compliance with the applicable regulations? Government regulation, namely OJK Regulation No. 11/POJK/03/2020. Studies This study attempts to illustrate how the South Tangerang City branch of Bank Maybank BSD supported the government's 2020 policies to combat the COVID-19 pandemic. The results demonstrated that PT. Bank Maybank BSD City branch South Tangerang supports the financial stimulus policy issued by Financial Services Authority by issuing policies restructuring/credit relief for customers affected by the COVID19 pandemic by adjusting the conditions of each customer, and policies restructuring/credit relief for customers affected by the COVID19 pandemic. The relief granted conforms to rule No. 11/POJK/03/2020.